Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s0967199409005498
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hyalin and sea urchin gastrulation. Part IV: a direct adhesion assay – progress in identifying hyalin's active sites

Abstract: SummaryIn Strongylocentrotus purpuratus the hyalins are a set of three to four rather large glycoproteins (hereafter referred to as "hyalin"), which are the major constituents of the hyaline layer, the developing sea urchin embryo's extracellular matrix. Recent research from our laboratories has shown that hyalin is a cell adhesion molecule involved in sea urchin embryo specific cellular interactions. Other laboratories have shown it to consist of 2-3% carbohydrate, and a cloned, sequenced fragment demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
(48 reference statements)
0
13
1
Order By: Relevance
“…The concentration of carbohydrate of H. grisea was 30% lower than that reported by Bechtel et al (2013) for the giant sea cucumber Parastichopus californicus from Alaska (USA). Sea urchins are poor in carbohydrate, but this substance has a significant role in both body coating and fertilization events (Ghazarian et al, 2010). Mol et al (2008) reported a concentration of 2.8% dw of carbohydrate in the roe of the sea urchin Paracentrotus lividus, which represents a carbohydrate content ~50-60% lower than those we found in the bodies of E. brasiliensis and L. variegatus.…”
Section: Carbohydratecontrasting
confidence: 53%
“…The concentration of carbohydrate of H. grisea was 30% lower than that reported by Bechtel et al (2013) for the giant sea cucumber Parastichopus californicus from Alaska (USA). Sea urchins are poor in carbohydrate, but this substance has a significant role in both body coating and fertilization events (Ghazarian et al, 2010). Mol et al (2008) reported a concentration of 2.8% dw of carbohydrate in the roe of the sea urchin Paracentrotus lividus, which represents a carbohydrate content ~50-60% lower than those we found in the bodies of E. brasiliensis and L. variegatus.…”
Section: Carbohydratecontrasting
confidence: 53%
“…There are four lines of evidence which suggest the presence of an appropriate substrate on the embryo surface. Firstly the work of Evans and Bosmann [21] showed the presence of glycosyltransferase activity in developing sea urchin embryos; secondly Latham et al[11], showed the presence of Con A ligands on the outside embryo surface and on the inner blastocoel surface; thirdly, exogeneously added hyalin that includes glucose residues causes similar developmental pathology to the effects reported here for glycosidases [5], and fourthly, Ghazarian et al [13], showed that periodate-treated hyalin blocked the ability of hyalin to cause developmental pathology. Latham et al [6] and Itza & Mozingo [7] showed that LCASW increased permeability of the embryo epithelium such that proteins could enter the blastocoel and that septate junctions mediating the barrier to permeability were loosened.…”
Section: Discussionmentioning
confidence: 52%
“…Past studies have implicated glycans and their binding partners in various sea urchin embryo cellular interactions, but definitive evidence for a glycan role(s) has been generally indirect [8, 9, 10, 11, 12, 13]. …”
Section: Introduction1mentioning
confidence: 99%
“…Fusion starts at the site of sperm entry and then traverses the oocyte in a wave to the antipode taking ~30 seconds to complete. Following the cortical reaction, a tightly adhering protective layer around the oocyte called the hyaline layer is formed, [10][11][12] while the peroxidase hardens the elevated fertilization membrane by cross-linking the tyrosine residues of the vitelline coat aided by hydrogen peroxide. This leads to a net increase in the total surface area of the plasma membrane, which can be observed as a transient increase in length of microvilli, and presumably changes the permeability and exchange properties of the oocyte with the environment.…”
Section: The Cortical Reactionmentioning
confidence: 99%